Are we ready for Open Science? On the spirit is willing, the flesh is weak - Pfuhl, Gerit (Septentrio Conference Series, 2019)
Watch the VIDEO. Scientists are curious, skeptical and critical. They try out new avenues, including open access publishing, but they might remain skeptical in adopting Open Science fully. There is thus conservatism in the publishing process itself that is independent of who pays for the article. But who to blame for a reluctance to provide open data, transparent experimental methods, or open peer review? I will argue that the culprit is the culture of academia which includes us researchers. The culture of academia is one of illusory freedom and full of traditions. It is also everything but immune of human biases and fallacies. Familiarity and fame influence where we publish, but also how we review and edit articles. As reviewers, our explorative nature lets us request fishing expeditions. As editors, being highly skeptical and critical, we may still misunderstand that a research hypothesis can lead to various statistical hypotheses. As authors, we may feel ownership of our data, confusing source with raw data. I have experienced – as an author of a pre-registered study with open data – the request to perform dubious additional statistical tests. As reviewer, I have more than once experienced that my request for more transparency and open data got rejected by editors. And as a journal editor, I have mixed experiences with authors making their data open, but also reviewers signing their peer review. Yes, it is often true that open data practices during the publishing process take time. But time is saved if appropriate data management practices are implemented before data is collected. However, the culture of academia fosters permanent time constraints preventing learning new techniques and tools, and as such supporting bad habits. Incentives to mitigate the bad habits need to address the entire research process. Incentives should aim at saving time for the individual, not reshuffling who pays what and when. In sum, there is willingness for Open Science, but not sufficient action.